Family Anesthesia Experience: Improving Social Support of Residents Through Education of Their Family and Friends - Susan M. Martinelli; Thanh N. Tran; Brooke A. Chidgey; Robert S. Isaak; Emily G. Teeter; Fei Chen (Association of American Medical Colleges, 2023)
Introduction The prevalence of burnout among anesthesiology residents is 41%-51%. Burnout is associated with medical errors, physician turnover, and substance use disorder. Social support and wellness may reduce burnout, but a barrier is support persons' lack of understanding of an anesthesiologist's work demands. We developed the Family Anesthesia Experience (FAX) to help support persons best support their resident. Methods FAX consisted of a 4-hour event with hands-on experience, didactics portion, and panel discussion. Participants learned about a typical day in the life of an anesthesiology resident, wellness, burnout, substance use disorder, and available support resources, and had hands-on experience with procedures. The panel discussion offered logistical information about anesthesiology residency and allowed support persons to ask panel members questions. A postevent survey collected feedback on the event. Results Fifty-one participants (first-year anesthesiology residents and their support persons) attended the event. Eight of 11 residents (73%) and 32 of 40 support persons (80%) completed the survey. All enjoyed the event, would recommend it to other anesthesiology resident support persons, and felt the event would improve communication and support. Most learned a moderate (35%) to large amount (50%) from the event. Qualitative feedback suggested most support persons found the event helpful in improving their understanding of anesthesiology residents' work demands. Discussion The FAX was well liked by participants. Although we did not assess specific knowledge gained and long-term effects of the 2022 event, evaluations of previous years' events suggest that the event improved participants' understanding of anesthesiology residents' work and stressors.